Cardioprotective effects of a selective c-Jun N-terminal kinase inhibitor in a rat model of myocardial infarction - Plotnikov, Mark B.; Chernysheva, Galina A.; Smolyakova, Vera I.; Aliev, Oleg I.; Fomina, Tatyana I.; Sandrikina, Lyubov A.; Sukhodolo, Irina V.; Ivanova, Vera V.; Osipenko, Anton N.; Anfinogenova, Nina D.; Khlebnikov, Andrei I.; Atochin, Dmitriy N.; et al. (Biomedicines)
Activation of c-Jun N-terminal kinases (JNKs) is involved in myocardial injury, left ventricular remodeling (LV), and heart failure (HF) after myocardial infarction (MI). The aim of this research was to evaluate the effects of a selective JNK inhibitor, 11H-indeno [1,2-b]quinoxalin-11-one oxime (IQ-1), on myocardial injury and acute myocardial ischemia/reperfusion (I/R) in adult male Wistar rats. Intraperitoneal administration of IQ-1 (25 mg/kg daily for 5 days) resulted in a significant decrease in myocardial infarct size on day 5 after MI. On day 60 after MI, a significant (2.6-fold) decrease in LV scar size, a 2.2-fold decrease in the size of the LV cavity, a 2.9-fold decrease in the area of mature connective tissue, and a 1.7-fold decrease in connective tissue in the interventricular septum were observed compared with the control group. The improved contractile function of the heart resulted in a significant (33%) increase in stroke size, a 40% increase in cardiac output, a 12% increase in LV systolic pressure, a 28% increase in the LV maximum rate of pressure rise, a 45% increase in the LV maximum rate of pressure drop, a 29% increase in the contractility index, a 14% increase in aortic pressure, a 2.7-fold decrease in LV end-diastolic pressure, and a 4.2-fold decrease in LV minimum pressure. We conclude that IQ-1 has cardioprotective activity and reduces the severity of HF after MI.